Ministry of Education Human Resource Management Practices and Internal Efficiency in Senior Secondary Schools Administration in Benue State - Dr. Mathew Sunday Dada; Tarfa Orvanya, Tarfa (Researchparks Publishing, 2022)
Management of human resource is a key factor in achieving organizational goals. Achieving internal efficiency requires relating organizational input and output. The study investigated the influence of Human Resource Management HRM practices of Benue State Ministry of Education on the internal efficiency of secondary education. The study answered four research questions and tested three hypotheses. Descriptive survey and correlational research designs were adopted. The population of the study was 305 school principals and vice from 23 Senior Secondary Schools spread across the 7 Local Government Areas in zone A. A sample size of 177 Principal and vice principals participated in the study selected by a multi Stage random sampling. Two instruments were used for the study; a self-constructed questionnaire title Benue State Ministry of Education Personnel Management Practices Questionnaire (BSMEPMPQ) and Secondary School Enrolment Proforma (SSEP). Four statistical tools were employed for data analysis; Mean, Percentage, Regression and t-test. The study revealed that BSMoE was rated low in compliance to the laid down teacher recruitment, deployment practices. The study established that the internal efficiency of secondary education was generally low. It was recommended that BSMoE should endeavour to follow the laid down teacher recruitment and deployment practices as enshrined in the civil service guidelines, doing this would improve teacher productivity for increase internal efficiency in the secondary education.